2021
DOI: 10.1002/ese3.1002
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous anodic alumina with ohmic contact between substrate and infill: Application to perovskite solar cells

Abstract: The use of a nanostructured aluminum substrate as the cathode for a perovskite photovoltaic device is described. This cathode consists of an aluminum substrate onto which a highly ordered array of aluminum oxide tubular pores was grown via anodization. The 1‐μm thick pores – arranged in a closed‐packed hexagonal pattern – were subsequently selectively etched at the bottom to remove the so‐called aluminum oxide barrier layer. The subsequent infiltration of the pores with the components of a methylammonium lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Using a similar concept, Montero‐Rama et al prepared a perovskite solar cell in which NAA–FPIs were used to contain the components of the device (i.e., titanium dioxide—TiO 2 , methylammonium lead iodide—MAPbI 3 , and spiro‐OMeTAD) and the aluminum substrate on its backside functions as the cathode. [ 184 ] Despite achieving a low PCE of 0.06%, this study demonstrated that NAA–FPIs can be filled with multiple materials to engineer their structure at the nanoscale and use the aluminum substrate on its backside as an ohmic contact. On the other hand, El‐Said et al used the aluminum substrate of NAA–FPIs containing Cu impurities as the photoanode in dye‐sensitized solar cells (DSSCs).…”
Section: Sunlight Harvesting Applications Of Naa–pcsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a similar concept, Montero‐Rama et al prepared a perovskite solar cell in which NAA–FPIs were used to contain the components of the device (i.e., titanium dioxide—TiO 2 , methylammonium lead iodide—MAPbI 3 , and spiro‐OMeTAD) and the aluminum substrate on its backside functions as the cathode. [ 184 ] Despite achieving a low PCE of 0.06%, this study demonstrated that NAA–FPIs can be filled with multiple materials to engineer their structure at the nanoscale and use the aluminum substrate on its backside as an ohmic contact. On the other hand, El‐Said et al used the aluminum substrate of NAA–FPIs containing Cu impurities as the photoanode in dye‐sensitized solar cells (DSSCs).…”
Section: Sunlight Harvesting Applications Of Naa–pcsmentioning
confidence: 99%
“…In the context of this perspective, the integration of NAA–PCs into solar cell systems has been explored to break through some of these technological bottlenecks, harnessing the unique geometric, optical, thermal, and electrically insulative properties of NAA to maximize photon‐to‐electron conversion rates in solar cell systems. In particular, NAA‐based Fabry–Pérot interferometers (NAA–FPIs) have been integrated into PV cells as scaffolds for PV materials, [ 184,185 ] radiative coolers, [ 186 ] electrodes, [ 184,187 ] and antireflective coatings. [ 163,164,188 ] NAA–FPIs are composed of straight cylindrical nanopores featuring a homogeneous distribution of effective refractive index in depth [23a] .…”
Section: Sunlight Harvesting Applications Of Naa–pcsmentioning
confidence: 99%
See 1 more Smart Citation